A Unified Perspective Review on Photon Dynamics, the Properties of Superfluid Free Space and Cosmic Phenomena (Global Journal of Science Frontier Research, 2025)
This perspective review presents a series of profound insights into the understanding of photon dynamics, fundamental constants, the properties of superfluid free space and cosmic phenomena. By integrating mechanical, electromagnetic, and cosmological perspectives, the author re-examines the Hubble constant, introduces dynamic super fluid free space polarization, and explores the Cosmic Microwave Background Radiation alongside fluctuation-dissipation processes. Central to this work is the theory of Elementary Super Photons, underpinned by the concept of superfluid free space as a dynamically polarizable grand medium linking all relatively moving particles and enabling dynamic equilibrium across the universe, which aligns well with March's Principle and non-local hidden variables in quantum mechanics. This ambitious framework unifies the dynamic behaviour of photons, the characteristics of dynamically polarizable superfluid free space, and key observable features of the cosmos. The theoretical advancements presented herein bridge classical mechanics, quantum mechanics and electromagnetism, fostering interdisciplinary exploration and laying the ground work for a deeper understanding of the universe's fundamental nature.
Keywords: superfluid free space; dynamic polarization; the hubble constant; fine-structure constant